Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T21:35:42+01:00
A) 2x-y=10
x+5y=-17/*(-2)
2x-y=10
-2x-10y=34
2x-y-2x-10y=10+34
-11y=44/:(-11)
y=-4
2x-(-4)=10
y=-4
2x+4=10
y=-4
2x=10-4
y=-4
2x=6/:2
y=-4
x=3

b) 3m+n=9 /*5
2m-5n=-11
15m+5n=45
2m-5n=-11
15m+5n+2m-5n=45-11
17m=34/:17
m=2
3*2+n=9
m=2
6+n=9
m=2
n=9-6
m=2
n=3

c) 4a-2=b
3a+7b=1,5
4a-b=2/*7
3a+7b=1,5
28a-7b=14
3a+7b=1,5
28a-7b+3a+7b=14+1,5
31a=15,5 /:31
a=0,5
28*0,5-7b=14
a=0,5
14-7b=14
a=0,5
-7b=14-14
a=0,5
-7b=0 /:(-7)
a=0,5
b=0

d) 5x=4-2y
4x+y=3
5x+2y=4
4x+y=3 /*(-2)
5x+2y=4
-8x-2y=-6
5x+2y=4
-8x-2y+5x+2y=4-6
-3x=-2 /:(-3)
x=⅔
5*⅔+2y=4
x=⅔
¹⁰/₃+2y=4
x=⅔
2y=4-¹⁰/₃
x=⅔
2y=⅔/:2
x=⅔
y=⅓

e) 6x-3y=9
x+5y=-9,5/*(-6)
6x-3y=9
-6x-30y=-57
6x-3y-6x-30y=9-57
-33y=-48
y=¹¹/₁₆
6x-3*¹¹/₁₆=9
y=¹¹/₁₆
6x-2 ¹/₁₆=9
y=¹¹/₁₆
6x=9+¹¹/₁₆
y=¹¹/₁₆
6x=9¹¹/₁₆ /:6
y=¹¹/₁₆
x=1⁵⁹/₉₆